Impact of nonthermal processing on different milk enzymes. (4th August 2019) - Ahmad, Talha; Butt, Muhammad Zubair; Aadil, Rana Muhammad; Inam‐ur‐Raheem, Muhammad; Abdullah,; Bekhit, Alaa El‐Din; Guimarães, Jonas T; Balthazar, Celso F; Rocha, Ramom S; Esmerino, Erick A; Freitas, Mônica Q; Silva, Márcia C; et al.
Abstract : Milk is highly perishable and deteriorates rapidly during storage. Although the thermal processing technologies successfully inactivate many enzymes and microorganisms up to a required level, they can negatively affect the natural flavour of dairy foods and decrease their nutritional value. Alternative nonthermal technologies have been established as an interesting approach to produce safe and healthy dairy products, without compromising their nutritional quality. These techniques have the ability to inactivate milk enzymes without affecting the milk quality. In addition, the combination of two different nonthermal techniques and mild heating has proven to be more effective to provide safety to milk when compared to the treatments alone. This review aims to evaluate the impact of nonthermal technologies, in particular, ultrasound, pulsed electric field, high‐pressure processing and ultraviolet irradiation on milk enzymes.